Female Rangers as Informal Community Educators: Khalifah Fil Ardh and Early Childhood Environmental Learning in Aceh - Samad, Munawwarah; Sri Astuti; Futhira, Nadia; Amelia, Lina; Abdurrahman Qahar, Jabbar; Maramina, Aula (Al-Athfal: Jurnal Pendidikan Anak, 2026)
Purpose – This study investigates how Female Rangers in Bener Meriah Regency operationalize the Islamic concept of khalifah fil ardh (human stewardship of the Earth) as a lived pedagogical practice within early childhood environmental education. It seeks to bridge the gap between eco-theological discourse and community-based educational praxis.Design/methods/approach – Employing a qualitative single-case study design, this research was conducted in Damaran Baru Village, Aceh. Data were generated through in-depth semi-structured interviews, participant observation, and document analysis. The analytical process followed an iterative model involving data condensation, data display, and conclusion drawing, complemented by inductive thematic coding to identify recurring patterns of practice and meaning.Findings – The findings reveal that Female Rangers enact dual and intersecting roles as grassroots conservation agents and informal educators. Their environmental engagement is not merely technical but deeply rooted in moral-religious consciousness, positioning ecological care as an ethical obligation. Pedagogically, their influence emerges through children’s situated participation in everyday ecological practices. Four core strategies underpin this process: (1) embodied modelling of pro-environmental behavior, (2) experiential learning through direct participation, (3) integration of spiritual reflection linking nature to divine responsibility, and (4) contextual embedding of environmental values within communal and cultural routines. These strategies collectively construct an implicit curriculum that integrates ecological awareness with moral and spiritual development in early childhood.Research implications/limitations – This study contributes to Islamic eco-theology by demonstrating how the notion of stewardship is translated into concrete pedagogical action within community contexts. It advances the conceptualization of informal environmental education as a relational and value-driven process. However, as a single-site qualitative inquiry, the findings are context-specific and not intended for statistical generalization, though they offer analytical transferability to similar socio-cultural settings.Practical implications – The study highlights the importance of synergizing formal education, community initiatives, and faith-based ecological values in designing early childhood environmental education. It suggests that integrating local actors such as Female Rangers into educational ecosystems can enrich children’s holistic development, particularly in fostering environmental ethics from an early age.Originality/value – The article offers a grounded account of how women-led conservation can operate as an informal pedagogical infrastructure through which young children encounter environmental care as part of moral, spiritual, and communal life.Paper type Research paper